1989
DOI: 10.1677/joe.0.1220451
|View full text |Cite
|
Sign up to set email alerts
|

The implication of opiates in the glucocorticoid-mediated inhibition of LH secretion in rats

Abstract: The present study was designed to test the effect of acute administration of dexamethasone on the postcastration and gonadotrophin-releasing hormone (GnRH)-induced rise of LH, and to examine whether the inhibitory action of glucocorticoids on LH secretion was mediated by the opioid system. Rats were castrated and injected 10-10.5 h later in a first set of experiments with saline, dexamethasone (250 micrograms/rat), nalmefene (2 mg/kg body weight) or nalmefene plus dexamethasone. The response to GnRH was tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Current findings suggest that EOP involvement may depend upon the nature and/or severity of the chronic stress stimulus, since opioid receptor antagonism can reverse chronic sur gical-[5], but not chronic restraint stress-induced de creases in circulating LH [37], The coexistence of GR with P-END [38] and CRF immunoreactivity [39][40][41] supports the possibility of a modulatory impact of gluco corticoids on neurons synthesizing these neuropeptides. Observations that DEX-induced decreases in plasma LH are reversed by opioid receptor antagonists [42,43] strengthen the hypothesis that proopiomelanocortin (POMC) peptide-producing neurons may function as neu ral substrates for central inhibitory effects of glucocorti coids on the GnRH-pituitary LH axis. Glucocorticoids also promote negative feedback inhibition of CRF synthe sis [44,45] and release [46] by paraventricular neurons.…”
Section: Discussionmentioning
confidence: 74%
“…Current findings suggest that EOP involvement may depend upon the nature and/or severity of the chronic stress stimulus, since opioid receptor antagonism can reverse chronic sur gical-[5], but not chronic restraint stress-induced de creases in circulating LH [37], The coexistence of GR with P-END [38] and CRF immunoreactivity [39][40][41] supports the possibility of a modulatory impact of gluco corticoids on neurons synthesizing these neuropeptides. Observations that DEX-induced decreases in plasma LH are reversed by opioid receptor antagonists [42,43] strengthen the hypothesis that proopiomelanocortin (POMC) peptide-producing neurons may function as neu ral substrates for central inhibitory effects of glucocorti coids on the GnRH-pituitary LH axis. Glucocorticoids also promote negative feedback inhibition of CRF synthe sis [44,45] and release [46] by paraventricular neurons.…”
Section: Discussionmentioning
confidence: 74%
“…An alternative possibil ity is that glucocorticoid effects on GnRH may be me diated by neuropeptidergic and/or monoaminergic neu rons; in fact, GR-like immunoreactivity has been local ized within nuclei of arcuate neurons immunolabeled for p-endorphin [62], neuropeptide Y [63,64], or dopamine [65]. Indeed, it has been reported that blockade of opiate receptors by nalmefene can prevent decreases in plasma LH observed 30 min after s.c. injection of DEX [8].…”
Section: Discussionmentioning
confidence: 99%
“…Specific receptors for these hormones have been detected within the anterior pituitary and central nervous system (CNS) [10][11][12][13][14][15][16][17][18], Al though glucocorticoids have been shown to exert diver gent effects on basal and/or gonadotropin-releasing hor mone (GnRH)-stimulated LH release in vitro by primary pituitary cell cultures [19][20][21][22][23], studies involving adminis tration of these steroids to pituitary tissue during short term perifusion have yielded more consistent results, in that glucocorticoids were found to have no effect upon basal LH, but to inhibit hormone release in response to GnRI I [9,23]. Although most reports indicate that gluco corticoids suppress pituitary responsiveness to an exoge nous GnRH challenge in vivo [4,5,7,9,24], steroid treat ment has been shown, under certain circumstances, to suppress plasma LH levels in vivo, without altering pitu itary GnRH receptor number or GnRH-induced LH release [7,8,[25][26][27], These latter observations lend sup port for a neural site(s) of inhibitory glucocorticoid ac tion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opioids are known to inhibit the reproductive axis. In the rat, dexamethasone reduces the postcastration rise in LH and opioid antagonists reverse the glucocorticoid-inhibiting effect on LH [15]. A recent study with rats [16]showed that the LH suppression obtained by intracerebroventricular and systemic administration of dexamethasone was blocked by pretreatment with naltrexone.…”
Section: Introductionmentioning
confidence: 99%